The Influence of Return on Asset and Debt Equity Ratio to Stock Prices: The Moderating Effect of Financial Performance of the Mining Industry - Maringka, Tonny Serfius (Universitas Brawijaya, Indonesia, 2024)
This research aims to test the moderator effect on characteristic variables such as return on assets and debt-equity ratio as exogenous variables on stock prices which are endogenous variables with return on equity being a proxy for financial performance. This research uses a quantitative approach with the path analysis method, the research object is 39 mining sector companies listed on the Indonesia Stock Exchange, a total of 156 companies studied. By using multiple linear regression analysis, the results obtained show that partial return on assets has a positive and significant effect on stock prices and the debt-equity ratio has a negative and significant effect on stock prices. Then the test uses moderator regression analysis where return on equity is proxied by financial performance as a moderator variable. The results show that the return on assets on share prices has a negative and significant influence. Meanwhile, the Debt Equity Ratio has a positive and significant effect on share prices. Appropriate financial asset allocation provides increased market expectations which will cause share prices to be valued higher. Asset management of mining industry companies does not show an increase in company value, in this case, return on equity, which should strengthen financial performance, and reduce share prices. On the contrary, conditions and information cause mining industry company share prices to fall. Management of return on equity well and accurately reflects financial performance, strengthening the relationship/influence of the debt-equity ratio on share prices.